Website Based Greenhouse Microclimate Control Automation System Design - Hafiz, Muhammad; Ardiansah, Irfan; Bafdal, Nurpilihan (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2020)
Microclimate control is very important for plants cultivation in a greenhouse, two of microclimate variables are temperature and humidity, this variable can be controlled using several methods, one option is to use the misting cooling system, but this process is still done manually. This study aims to create a greenhouse microclimate control system that can be automatically displayed and controlled via a website. This research uses engineering design methods. The results show that the system can automatically turn on the misting cooling system when temperatures are above 30 ℃ and RH below 80%. Greenhouse microclimate data can be displayed and controlled via a website. The UV index greatly influences the performance of the misting cooling system on temperature and RH conditions in the greenhouse, while the UV index rises to 12 the temperature cannot be lowered and RH cannot be increased, but when the UV index falls from 12 the temperature can be reduced by ± 3 ℃ and RH can be increased by ± 12%.